Pelatihan Pencegahan Bahaya Rabies - Renika, Renika; Dzulkifli, Sri; Maswan, Maswan; Maulidi, Indah Sikri; Parisy, Aldy Al; Wahyuni, Indah; Rastina, Rastina; Darminto, Andi Ogo (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muslim Maros, 2024)
The majority of the people of Benteng Tellue Village (Amali District) keep dogs as pets in their homes and it is a habit to carry them when farming in the fields and also use them to hunt wild pigs. One thing that is of common concern is that the public still lacks information about rabies and the prevention efforts that can be taken. Therefore, rabies training activities are an appropriate means to directly meet and conduct questions and answers with the community in Benteng Tellue Village, Amali District, Bone Regency. The community is expected to share and disseminate information to other family members. The results of the activity showed an increase in public knowledge after education was carried out regarding preventing rabies in dogs. Increasing public understanding about rabies is very necessary through training methods.